2015
DOI: 10.1128/iai.02925-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Carboxy Terminus of SecA in Iron Acquisition, Protein Translocation, and Virulence of the Bacterial Pathogen Acinetobacter baumannii

Abstract: Acinetobacter baumannii is a Gram-negative opportunistic nosocomial pathogen that causes pneumonia and soft tissue and systemic infections. Screening of a transposon insertion library of A. baumannii ATCC 19606 T resulted in the identification of the 2010 derivative, which, although capable of growing well in iron-rich media, failed to prosper under iron chelation. Genetic, molecular, and functional assays showed that 2010's iron utilization-deficient phenotype is due to an insertion within the 3= end of secA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The 24-h time point was chosen for RNA isolation because there was not apparent hemolytic activity until this time. RNA isolation, cDNA synthesis and qRT-PCR analyses were performed as previously described [43]. Briefly, bacterial cells were lysed in lysis buffer [0.3 M sodium acetate (pH 4.0), 30 mM EDTA and 3% SDS] previous to RNA purification following the manufacturer’s protocol included with the Maxwell 16 LEV simplyRNA Tissue Kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…The 24-h time point was chosen for RNA isolation because there was not apparent hemolytic activity until this time. RNA isolation, cDNA synthesis and qRT-PCR analyses were performed as previously described [43]. Briefly, bacterial cells were lysed in lysis buffer [0.3 M sodium acetate (pH 4.0), 30 mM EDTA and 3% SDS] previous to RNA purification following the manufacturer’s protocol included with the Maxwell 16 LEV simplyRNA Tissue Kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as previously reported (22). The isochorismatase parental allele was PCR amplified by using total strain 98–37–09 DNA as a template, Pfu DNA polymerase, and primers (forward: 5′‐CGGGATCCATGAAACAAGCACTATTAGTTATC‐3′; and reverse: 5′‐CGCCTAGGTTAAGATTTTGCTAGAAAGTCAG‐3′), both of which included BamHI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies conducted by prominent laboratories have demonstrated that iron or zinc limitation can suppress Acinetobacter growth and that the organisms have multiple iron and zinc acquisition mechanisms, including catechol production, production of very high-affinity siderophores (e.g., acinetobactin) and companion siderophore uptake receptor and energetic mechanisms, and heme utilization (82,121,(308)(309)(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320). Small-molecule iron chelators have in vitro activity at killing Acinetobacter during log growth (318).…”
Section: Trace Metal Sequestrationmentioning
confidence: 99%